Prognostic significance of signal transducer and activator of transcription 5 and 5b expression in Epstein–Barr virus‐positive patients with chronic lymphocytic leukemia. (1st July 2016) - Diamantopoulos, Panagiotis T.; Sofotasiou, Maria; Georgoussi, Zafiroula; Giannakopoulou, Nefeli; Papadopoulou, Vasiliki; Galanopoulos, Athanasios; Kontandreopoulou, Elina; Zervakis, Panagiotis; Pallaki, Paschalina; Kalala, Fani; Kyrtsonis, Marie‐Christine; Dimitrakopoulou, Aglaia; et al.
Abstract: Signal transducer and activator of transcription (STAT) proteins have been intensively studied in hematologic malignancies, and the efficacy of agents against STATs in lymphomas is already under research. We investigated the expression of total STAT5 and STAT5b in peripheral blood samples of patients with chronic lymphocytic leukemia (CLL) in correlation with the presence of Epstein–Barr Virus (EBV) and its major oncoprotein (latent membrane protein 1, LMP1). The EBV load was measured in the peripheral blood by real‐time PCR for the BXLF1 gene and the levels of LMP1 by PCR and ELISA. Western blotting was performed for total STAT5 and STAT5b in protein extracts. STAT5b was only expressed in patients (not in healthy subjects) and STAT5 but particularly STAT5b expression was correlated with the presence of the virus (77.3% vs. 51.2%, P = 0.006 for STAT5b) and to the expression of LMP1 (58.3% vs. 21.6%, P = 0.011 for STAT5b). Moreover, the expression of STAT5b and the presence of EBV and LMP1 were strongly negatively correlated with the overall survival of the patients (log‐rank test P = 0.011, 0.015, 0.006, respectively). Double positive (for EBV and STAT5b) patients had the lowest overall survival (log‐rank test P = 0.013). This is the first report of a survival disadvantage of EBV+ patients with CLL, and the first time that STAT5b expression is correlated with survival. The correlation of STAT5 expression with the presence of the virus, along with our survival correlations defines a subgroup of patients with CLL that may benefit from anti‐STAT agents. Abstract : The role of signal transducer and activator of transcription proteins has been investigated in viral lymphomagenesis. We investigated the expression of total signal transducer and activator of transcription (STAT5), and STAT5b in particular, in patients with chronic lymphocytic leukemia. STAT5b was correlated with the presence of Epstein–Barr virus. Moreover, its expression was correlated with shorter overall survival of the patients. Double positive (Epstein–Barr Virus /STAT5b) patients had the lowest overall survival, thus, defining a group of patients that could benefit from the developing anti‐STAT agents.